Preservice Science Teachers' Opportunities for Learning Through Reflection When Planning a Microteaching Unit. Issue 1 (2nd January 2019) - Karlström, Matti; Hamza, Karim
ABSTRACT: Although microteaching is a common approach to engaging preservice teachers in reflection on teaching in on-campus courses, this reflection is usually carried out as a separate part. We examined how preservice middle school science teachers reflected amid planning a 20-min microteaching unit on sustainable development. Six groups of preservice teachers were video recorded and their conversations transcribed. We used practical epistemology analysis to analyze moments of reflection in these conversations. The preservice science teachers recurrently engaged in reflection in the course of their planning, which led to changes in perspective concerning important aspects of how to plan teaching that may be considered central for preservice science teachers to learn during their teacher education. Preservice teachers' reflection was related to the openness of the task, as they had to make decisions about many different aspects of their teaching. Even aspects that are not on the table in a real-world setting, for instance having the possibility of deciding on the age of the target students, led to productive reflection and opportunities for learning. Our results contribute to increased awareness of the possibilities of microteaching for facilitating learning during planning. This may provide science teacher educators with better possibilities of supporting their preservice science teachers' reflective practice.